Bibliography of Phasmida (Insecta) - V. (1930-1939). - Carlberg, Ulf (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The literature on the stick- and leaf-insects (order Phasmida) published during the period 1930 to 1939 has been listed. 231 scientific papers, chapters in books, thesises, reports etc. are listed. A systematic index is included.